Gender differences in the utilisation of surgery for congenital heart disease in India. Issue 23 (7th June 2011) - Ramakrishnan, Sivasubramanian; Khera, Rohan; Jain, Snigdha; Saxena, Anita; Kailash, Suparna; Karthikeyan, Ganesan; Kothari, Shyam S; Juneja, Rajnish; Bhargava, Balram; Kalaivani, Mani; Mehta, Manju; Bahl, Vinay K; et al.
Abstract : Background: Corrective surgery for congenital heart disease may be life-saving, but its utilisation depends upon several social and economic factors. Girls with cardiac defects may not receive equitable care in India, but this has not been systematically studied. Methods: In this prospective study, parents or guardians of 405 consecutive children aged up to 12 years (mean±SD age 3.43±3.44 years; 271 boys) who had been advised to undergo elective paediatric cardiac surgery were interviewed using a validated questionnaire. The status of the patients was reviewed after a year and the factors associated with non-compliance with treatment were analysed. In a qualitative sub-study the parents of 20 children who had not undergone surgery were interviewed. Qualitative data were analysed using an inductive analytical approach. Results: Of the 405 patients studied, 44% (59/134) of girls had undergone surgery at 1 year compared with 70% (189/271) of boys (χ 2 =24.97; p<0.001). Independent predictors for non-compliance with surgery included female gender (OR 3.46, 95% CI −2.06 to 5.80; p<0.0001), lower socioeconomic classes (lower-middle: OR 18.62, 95% CI −2.14 to 161.8, p=0.008; upper-lower: OR 34.27, 95% CI −3.72 to 316.0, p=0.002) and higher cost of surgery (OR 1.92, 95% CI −1.06 to 3.47, p=0.03). In the in-depth interviews, apprehensions about future matrimonial prospects of girls and lack of social support emerged as the major factors responsible for delays in undergoing surgery. Conclusions: Female gender is an important determinant of non-compliance with paediatric cardiac surgery. Deep-seated social factors underlie this gender bias.